2016
DOI: 10.1152/ajpregu.00115.2015
|View full text |Cite
|
Sign up to set email alerts
|

Proton channels and renal hypertensive injury: a key piece of the Dahl salt-sensitive rat puzzle?

Abstract: O'Connor PM, Guha A, Stilphen CA, Sun J, Jin C. Proton channels and renal hypertensive injury: a key piece of the Dahl salt-sensitive rat puzzle? Am J Physiol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…; O'Connor et al. ). Moreover, in both renal tubular epithelial cells and peritoneal macrophages, Hv1‐dependent ROS production was enhanced by low intracellular Na + or by NHE‐1 inhibition (Jin et al.…”
Section: Discussionmentioning
confidence: 99%
“…; O'Connor et al. ). Moreover, in both renal tubular epithelial cells and peritoneal macrophages, Hv1‐dependent ROS production was enhanced by low intracellular Na + or by NHE‐1 inhibition (Jin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Given the known biophysical characteristics of Hv1 5 , localization of this channel to the outer-mitochondrial membrane may provide explanation for the seemingly low activation threshold required to observe functional effects of Hv1 in mTAL. That is, by residing on a membrane with low potential difference, mitochondrial Hv1 may open more easily than Hv1 localized to the cell membrane where membrane potential is −60 to −80mV in mTAL [15]. Both NH 4 Cl loading and osmotic stress appeared to increase mitochondrial membrane potential in mTAL from wild-type animals.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of mTAL ROS production by osmotic stress : We have previously shown that osmotic stress promotes ROS production in mTAL [11]. We have utilized this stimuli to identify differences in mTAL ROS production between Dahl salt-sensitive rats and salt-resistant resistant control strains [11], and this stimuli was utilized to identify Hv1 as critical to the formation of ROS production in mTAL [15]. Given this, to investigate the molecular source of Hv1 dependent ROS production in mTAL, we investigated the incrementing bath NaCl concentration on ROS production in mTAL from male wild-type (n = 6), NOX4 −/− (n = 7) and p67phox −/- (n = 7) Dahl salt-sensitive rats.…”
Section: Methodsmentioning
confidence: 99%
“…ROS can regulate ion transport 1618,23,3564 . Superoxide, produced by NADPH oxidase, enhances NaCl transport in the renal proximal tubule 16,17,39,44,45,59 , thick ascending limb of Henle 41,46,48 , and collecting duct 18,47,48 . The voltage-gated proton channel participates in the increased production of superoxide in the renal outer medulla of Dahl salt-sensitive rats 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Superoxide, produced by NADPH oxidase, enhances NaCl transport in the renal proximal tubule 16,17,39,44,45,59 , thick ascending limb of Henle 41,46,48 , and collecting duct 18,47,48 . The voltage-gated proton channel participates in the increased production of superoxide in the renal outer medulla of Dahl salt-sensitive rats 46 . It should be born in mind, however, that ROS can inhibit Na + /K + -ATPase and NHE3 activity in the renal proximal tubule 48,5053 .…”
Section: Introductionmentioning
confidence: 99%